The impact of Christianity on traditional agricultural practices and beliefs among the Kimaragang of Sabah: a preliminary study - Low, Kok On; Jacqueline Pugh-Kitingan (Nanzan University, 2015)
The Kimaragang, an indigenous Dusunic ethnic group from the Districts of Kota Marudu and Pitas in Sabah, Malaysia (formerly North Borneo), traditionally practice the shifting cultivation of hill rice with maize. This study focuses on Kimaragang hill rice cultivation and discusses some of their traditional agriculturally-focused beliefs and communal healing and cleansing rituals. Over time, with the conversion to Christianity and the movement towards the towns of Tandek and Kota Marudu, many of these practices have declined. Christianity became the main religion among the Kimaragang during the 1950s and more so after the expulsion of missionaries from Sabah in the early 1970s. The factors that led to this large-scale conversion to Christianity and the gradual demise of some of the old agricultural rituals and some of the associated beliefs are herein examined. Other factors for this decline are also discussed.